The Double-Leucine Motifs Affect Internalization, Stability, and Function of Organic Anion Transporting Polypeptide 1B1 - Xuyang Wang; Jieru Chen; Jiujiu Huang; Mei Hong (MDPI AG, 2023)
Organic anion transporting polypeptide 1B1 (OATP1B1) is specifically expressed at the basolateral membrane of human hepatocytes and plays important roles in the uptake of various endogenous and exogenous compounds including many drugs. The proper functioning of OATP1B1, hence, is essential for the bioavailability of various therapeutic agents and needs to be tightly regulated. Dileucine-based signals are involved in lysosomal targeting, internalization, and trans-Golgi network to endosome transporting of membrane proteins. In the current study, we analyzed the 3 intracellular and 13 transmembrane dileucine motifs (DLMs) within the sequence of OATP1B1. It was found that the simultaneous replacement of I332 and L333 with alanine resulted in a significantly reduced level of the mature form of OATP1B1. The cell surface expression of I332A/L333A could be partially rescued by MG132, as well as agents that prevent clathrin-dependent protein internalization, suggesting that this dileucine motif may be involved in the endocytosis of OATP1B1. On the other hand, I376/L377 and I642/L643, which are localized at transmembrane helices (TM) 8 and 12, respectively, are involved in the interaction of the transporter with its substrates. I642A/L643A exhibited a significantly decreased protein level compared to that of the wild-type, implying that the motif is important for maintaining the stability of OATP1B1 as well.